Martin Seligman’s Theory in the Perspective of Positive Psychology - Liu, Shuting (International Journal of Social Sciences and Public Administration, 2024)
Happiness is people’s eternal pursuit of the goal, but in the pursuit of the road, some people will lose themselves because of the arrival of setbacks and difficulties, forget their original heart, or because of the pressure of modern social life leads to a variety of psychological problems. People should keep their positive and optimistic attitude to achieve their goals in today’s society. Through the collection and analysis of literature review, this paper mainly introduces several theories related to happiness from the perspective of positive psychology by Martin Seligman, the father of positive psychology, with the purpose of allowing people to understand how negative thinking patterns are produced and some measures can be taken to improve their positive thinking. At the same time, this paper also points out the limitations of these theories and some critical thinking and makes an in-depth exploration of the emergence and formation of these theories.